Policy or privacy - what matters most for individual well-being? Determinants of life satisfaction in the enlarged Europe - Petra Böhnke (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2007)
Life satisfaction is quite heterogeneously distributed across countries of the enlarged European Union. Previous research has shown how living conditions within individual countries, such as access to material and emotional resources, are important for personal well-being, but it has neglected to explain differences between countries. This article investigates whether it also matters in which political, economic, and social circumstances people live, as well as whether their particular perception of the quality of their societal environment plays a role. People are well aware that the institutional and cultural settings in which their lives are embedded create opportunities and limitations: within individual countries, perceptions of society influence life satisfaction outcomes irrespective of access to resources. However, their importance for well-being differs across Europe: perceptions of society and material resources are highly decisive in countries which provide only a minimum of social security and in which the reliability of political institutions is poor. In rich and stable countries, the impact is weaker and private social support becomes more important. In addition to these country-specific weights of life satisfaction determinants, life satisfaction variations between countries can be explained to a large extent by taking into consideration the economic performance, the social security level, and the political culture in a country - all in all, general conditions that enable people to live a respectable life.
Keywords: 300; Lebenszufriedenheit; Lebensqualität; EU-Staaten